Food Sanitation and Hygiene Practice in Foods Purchasing during the Early Period of Covid19 Pandemic in Greater Jakarta, Indonesia: An Online Study - Arfines, Prisca Petty; Sitorus, Nikson; Saptarini, Ika; Rosha, Bunga Christita; Amaliah, Nurillah (JURNAL KESEHATAN LINGKUNGAN, 2022)
Introduction: The Covid19 pandemic has greatly impacted all aspects of life, including the behavior of food purchasing. This study aims to identify the description of food hygiene and sanitation practices as part of the food safety aspect in the practice of food purchasing in Greater Jakarta, Indonesia. Methods: Data collection was conducted online in May 2020 from 411 respondents including data on sociodemographic, the proxy of knowledge level, perceptions, sources of information related to food handling, and the practice of food sanitation, and hygiene during the pandemic. Food sanitation and hygiene practices were assessed using a composite index of variables based on the Five Keys to Safer Food and preventive measures during the pandemic. Logistic regression analysis was conducted to assess factors associated with food sanitation and hygiene practices. Results and Discussion: Sufficient practice on food sanitation and hygiene is still relatively low (41.6%). An increased risk of poor food sanitation and hygiene practices was observed in people with less attention on the virus transmission while doing direct shopping, had a non-permanent job, single source of information on food handling during a pandemic, and were currently not married. Changes in the frequency of direct food purchasing and method of online food purchasing were shown as protective factors to better food and sanitation hygiene practice. Conclusion: The food sanitation hygiene practices of consumers during the pandemic in Indonesia are classified as unfavorable. Educational interventions using multi-source of media information are recommended to promote good hygiene food sanitation practices during the pandemic.